Future Studies and Counterfactual Analysis Seeds of the Future - Gordon, Theodore J.; Todorova, Mariana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
In this volume, the authors contribute to futures research by placing the counterfactual question in the future tense. They explore the possible outcomes of future, and consider how future decisions are turning points that may produce different global outcomes. This book focuses on a dozen or so intractable issues that span politics, religion, and technology, each addressed in individual chapters. Until now, most scenarios written by futurists have been built on cause and effect narratives or depended on numerical models derived from historical relationships. In contrast, many of the scenarios written for this book are point descriptions of future discontinuities, a form allows more thought-provoking presentations. Ultimately, this book demonstrates that counterfactual thinking and point scenarios of discontinuities are new, groundbreaking tools for futurists.
Chapter 1: Introduction -- Chapter 2: True or False: The Problem Here is Identifying What is True and What is Not -- Chapter 3: Proliferation: Doomsday or Politics? The Problem Here is Controlling Spread of Weapons of Mass Destruction -- Chapter 4: The Bounds of Humanity: Will Malthus Ultimately Be Proven Correct? The Problem Here is that We Don't Know How to Limit Population Growth or if New Policies are Really Necessary. Can We Leave it to Chance? -- Chapter 5: The Beginning and Hereafter: Why do We Exist? -- Chapter 6: Immortality: Where Does the Need to be Remember -- Chapter 7: Religion: The Problem Here is that in Religion, as well as Other Institutions, We See Corruption, Immorality, Ethical Lapses, and Abuses. In its Entwinement with Government: Who Makes and Enforces Laws, Sets Education Standards, and Provides Security: the People, the King, or God? -- Chapter 8: Decision Making: The Talent for Decisions. The Problem Here is that Most Decisions Turn out Badly -- Chapter 9:Dealing with Bio-terrorism: The Problem Here is that Terrorism can Adopt Biological Weapons as an Attack Mode: Harder to Detect, More Dangerous in its Outcome -- Chapter 10: Our Computer Overlords: The Problems Here are the Contest Between Work and Leisure, How Much of Each, Who has Either and the Chances for AI Becoming our Masters -- Chapter 11: What Constitutes Progress? The Problem Here is Defining What Constitutes Progress and MEans for Attaining it Since Science, Technology, Politics, and Markets do not Necessarily Follow Paths tha tLead to Solutions of Pressing Problems or Attainment of Goals -- Chapter 12: Political Chaos: The Problem Here is What Politics Has Become. Civility is Almost Gone, Debate is Almost Non-existent, yet the Sides are Firm in Their Positions and Sure They are Right -- Chapter 13: The Perfect Human: Unlocking the Mysteries of Human Genetics and Developing the Technologies to Manipulate Heredity Will Give, for Better or Worse, a New Dimension to Our Ability toSet the Fate of Our Children -- Chapter 14: Conclusions -- Appendix A Methodologies -- Appendix B Authors' Biographies -- Index.
Keywords: Science -- Social aspects; Artificial intelligence; Technological innovations; Science and Technology Studies; Artificial Intelligence; Innovation and Technology Management